The Role of Self-Efficacy, Hardiness, and Coping Strategies in Predicting Self-Care Behaviors in Patients with Type 2 Diabetes - Soroor Arshi; Maryam Kalhornia Golkar; Hassan Ahadi; Mastoreh Sedaghat (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Diabetes is a chronic disease that, without proper care, leads to a rise in blood sugar and, in the long term, disrupts the functions of various tissues and organs of the body. Therefore, self-care seems to be particularly important to reduce the injuries associated with this disease. Objectives: The aim of this study was to investigate the role of coping strategies, self-efficacy, and hardiness in predicting self-care behaviors in patients with type 2 diabetes. Methods: This was a descriptive-correlational study. The statistical population of this study included all patients with type 2 diabetes referred to medical centers in Khomeini Shahr, Isfahan-Iran, among whom 200 subjects were selected by convenience sampling. For data collection, Niknami (2013) self-care, Kubasa (1976) hardiness, Scherer self-efficacy, and Lazarus and Folkman coping strategies questionnaires were used. Data analysis was performed using stepwise multiple regression using SPSS software version 26. Results: The mean (SD) age of the participants was 48.54 (7.62) years, and women constituted 72% of the participants. The results showed that self-efficacy (53%, p=0.001) and hardiness (31%, p=0.008) had the largest shares in explaining self-care behaviors of patients with type 2 diabetes. The results also showed that coping strategies did not significantly influence the self-care behaviors of patients with type 2 diabetes (p<0.05), so it was excluded from the model. Conclusion: According to our findings, self-care behaviors of diabetic patients can be improved by boosting their hardiness and self-efficacy.